2021
DOI: 10.22225/jj.8.2.2021.202-208
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Attitude in Mediating Environmental Knowledge towards the Purchase Intention of Green Cosmetic Product

Abstract: The existence of public awareness of environmental preservation today, makes many companies, especially cosmetics, try to put forward the ecological aspects and raise environmental issues as one of their marketing strategies. This study aims to explain attitudes and environmental knowledge in determining the purchase intention of a green cosmetic product. This study uses a purposive sampling technique for determining samples. The samples used were 100 people, all consumers who had never bought green cosmetic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
9
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 5 publications
(5 reference statements)
5
9
0
3
Order By: Relevance
“…When environmental knowledge increases, there is a corresponding increase in halal-green awareness of the products consumed. The findings of this study support the results of the study by Rashid (2009), Gao et al (2016) and Putri et al (2021), which found that there consumer green awareness influences environmental knowledge.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…When environmental knowledge increases, there is a corresponding increase in halal-green awareness of the products consumed. The findings of this study support the results of the study by Rashid (2009), Gao et al (2016) and Putri et al (2021), which found that there consumer green awareness influences environmental knowledge.…”
Section: Discussionsupporting
confidence: 90%
“…H4 , which states that environmental knowledge affects consumer attitudes toward environmentally friendly halal cosmetics, is also verified in this study. This study’s findings confirm the research findings of Suki et al (2016) and Putri et al (2021), that environmental knowledge has a positive and significant impact on consumer attitudes. The greater the environmental knowledge, the more positive the consumer attitude is toward environmentally friendly products.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations